Plasmid-Mediated Fluoroquinolone Resistance Genes in Quinolone-Susceptible Aeromonas spp. Phenotypes Isolated From Recreational Surface Freshwater Reservoir - Kosikowska, Urszula; Stec, Joanna; Andrzejczuk, Sylwia; Mendrycka, Mariola; Pietras-Ożga, Dorota; Stępień-Pyśniak, Dagmara (Frontiers in Cellular and Infection Microbiology, 2022)
Aeromonas spp. are recognized as opportunistic pathogens causing diseases. Infections in humans can result mainly in gastrointestinal and wound diseases with or without progression to septicaemia. Although Aeromonas spp. are not known uropathogens and they rarely cause urinary tract infection (UTI) we hypothesise that presence of these bacteria in the water and the contact during the e.g. recreational and bathing activity can create the conditions for the colonization of human body and may effect to diseases with various localization including the urinary tract. Our study presents the occurrence of aeromonads fluoroquinolone-sensitive phenotypes with the presence of plasmid-mediated fluoroquinolone-resistance (PMQR) genes in the natural freshwater reservoir occasional use for recreational activity. Sixty-nine isolates collected during the bathing period were identified by mass spectrometry and screened for the presence of fluoroquinolone resistant phenotypes and genotypes. Fluoroquinolones susceptibility was determined as MIC (minimal inhibitory concentration) values. PMQR qnr-genes were detected by PCR. Isolates comprising eight species, namely mainly A. veronii (50.7% isolates), A. media (24.6% isolates), and rarely A. eucrenophila, A. caviae, A. bestiarum, A. ichthiosmia and A. hydrophila, were selected. All isolates were phenotypically sensitive either to ciprofloxacin and levofloxacin. Unexpectedly, at least one to three of the PMQR gene was detected in 42.0% of the fluoroquinolone-susceptible Aeromonas spp. phenotypes. Mainly the qnrS (34.8% isolates) and qnrA (14.5% isolates) determinants were detected. Two determinants simultaneously were detected in three isolates: qnrA and aac(6’)-Ib – in one isolate of A. veronii, and qnrS and aac(6’)-Ib – in one isolate of A. veronii and one isolate of A. caviae. In conclusion, freshwater reservoir occasional use for bathing was tainted with aeromonads with a high occurrence of opportunistic pathogens A. veronii and A. media. MALDI‐TOF MS is a powerful technique for aeromonads identification. Our data reveals the mismatch phenomenon between fluoroquinolone-sensitive aeromonads phenotypes and presence of plasmid-mediated qnr-resistance-genes. It suggests that phenotypically-susceptible bacteria might be a potential source for storage and transmission of these genes. The exposure during the recreational activity may create of the potential risk for causing infections difficult both diagnostically and therapeutically after expressing the resistance-genes and quinolone-resistant strain selection.